Análise estrutural da rizogênese adventícia de Acacia mearnsii de wild. e de Ilex paraguariensis A. ST.-Hil - Santos, Marjana Machado dos (2023)
The objective of this work was the anatomical description of the rhizogenesis of minicuttings, from clones selected from the adventitious rooting of A. mearnsii (black wattle) and I. paraguariensis (yerba mate), as well as to bring new insights on how barriers can affect adventitious rooting. For this purpose, anatomical characteristics of semi-hardwood minicuttings clones of A. mearnsii and I. paraguariensis treated with indolbutyric acid (IBA), grown in polyethylene trays with commercial substrate based on pine bark, coarse grained sand and medium vermiculite were analyzed. , kept in a humid chamber. Black wattle minicuttings (B5, AB6, A1845) were collected at intervals of 0, 1, 5, 10, 15 and 30 days and yerba mate clones (13SM05, 10SM07, 06SM15) were collected at 0, 30 and 60 days. Histochemical tests were performed to detect the presence of starch, and primary and secondary metabolites with rhizogenesis. The place of origin of the root primordia was verified. The general results contributed to understand the rooting process of both species, and black wattle, regardless of the sclerenchyma layer in the phloem region, was not an anatomical barrier here for the present study, since the formation of roots occurred in a endodermal proliferation, vascular tissue and primary and secondary phloem activity to form new cells. In black wattle, it was also verified that the absence of tissue, due to the occurrence of fungi in the first hours of cultivation, appeared as such an environmental barrier, for these studied clones. In yerba mate, the presence of starch in abundance was remarkable in clones with greater rooting competence, whereas for black wattle it was indifferent. He also observed that small differences between species may be associated with the response speed for adventitious rooting. However, the formation of adventitious roots in both species and studied clones showed similarity, from callus formation, adventitious vascularization and root formation by the indirect pattern. Therefore, for both studied species, rhizogenesis presented barriers, but these are not necessarily anatomical.